From Training to Competition: The Effects of a Strategic Self-Talk Intervention on Pre-Competition Anxiety and Self-Confidence in Young Swimmers - Galanis, Evangelos; Mylonopoulos, Aggelos; Comoutos, Nikolaos; Theodorakis, Yannis; Hatzigeorgiadis, Antonis (Inquiries in Physical Education and Sport, 2022)
The purpose of the present study was to investigate the effects of a strategic self-talk intervention on young swimmers’ pre-competition anxiety and self-confidence in actual competitive conditions. Participants were 38 swimmers (16 males and 22 females) with a mean age of 14.71 (± 1.39) years and mean competitive experience 6.15 (± 1.74) years. The intervention took place in-between two qualifying for the national championship competitions, which were scheduled in the national calendar eight weeks apart one from the other. Pre-competition anxiety and self-confidence were assessed in these competitions. Accordingly, the intervention lasted eight weeks during which the experimental group was educated and trained in the use of strategic self-talk, while the control group received the same swimming training but without self-talk. Overall, the results showed that in the competition following the intervention, for the experimental group cognitive anxiety was reduced and self-confidence was increased, whereas no changes were observed for the control group. The findings suggest that strategic self-talk is an effective strategy for regulating anxiety and self-confidence in competitive settings, and provide support for postulations that anxiety regulation may be among the mechanisms explaining the facilitating effects of self-talk on performance.